(3GdEjVGM eeG jSCd Yfg GdWHQjhfs - (3CMeO Hf jMjis
(3ChdgG (B:s
(3GdMeO ddg GdPi YdG Yf OQc GdeNdhbjf hLd SHMGfg Yf Xde GdeJYHOjf, GdUGOb ai hYOg hhYjOg s
(3BNQgG (B:s
(3heG cGf ef CSHGH GdBNQI heG Mce Gddg Hg dgG agh GdKGHJ GdHGbi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdCNjQs
(3HChQGbgG JbWjY hJQejes
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3eLGejY (B102) s
Keywords: (3GdbQGAGJ hGdJLhjOs